Overview of Leishmaniasis - ALsheibany, Sheimaa J. (Journal of Science in Medicine and Life, 2025)
Leishmaniasis is a disease through a parasitic organism that invades and thrives within human cells when a sand fly takes a blood meal from the infected person. This specie is commonly found in Asia, Africa, the Americas, and the Mediterranean region. Annually, there are 1. 50 to 200 new cases of Leishmaniasis every year with about three hundred and fifty million people at risk of getting the disease. In addition, Leishmaniasis is a major killer which claims 70, 000 lives every year. The clinical manifestations depend on the apropos Leishmania species and its host’s immunological responses. These manifestations can occur restricted to the skin or may involve internal organs and, in some cases, may be fatal. It has diverse medications employed in its therapy, yet the single effective cure is realized through the existing antimonies in today’s dispensary.